Thrombotic microangiopathy in a patient with adult‐onset Still's disease. Issue 11 (20th May 2014) - Rawal, Shail; Einbinder, Yael; Rubin, Laurence; Perl, Jeff; Trinkaus, Martina; Teitel, Jerome; Pavenski, Katerina
<x xml:space="preserve">Abstract</x> Background Since there are many disorders that can present with thrombotic microangiopathy (TMA), establishing a correct diagnosis is important to offer the most appropriate therapy. Case Report A 26‐year‐old woman was transferred to our hospital with fragmentation hemolytic anemia, thrombocytopenia, and acute kidney failure. History revealed that she was recently diagnosed with adult‐onset Still's disease (AOSD) and received intraocular injections of bevacizumab to treat acute retinal artery occlusion. At our hospital, she underwent extensive investigations and was treated with high‐dose steroids, hemodialysis, and therapeutic plasma exchange. For recurrent disease, she received a single dose of eculizumab. Results The patient's ADAMTS13 activity was normal and she had evidence of complement activation. Genetic testing identified a benign polymorphism in the C3 gene. Pathophysiology of TMA in AOSD is briefly discussed and an overview of the literature is presented. Conclusion Work‐up of a new fragmentation hemolytic anemia and thrombocytopenia should include careful review of past history, including medications, as well as relevant laboratory investigations with aim to establish a correct diagnosis. Occasionally, the correct diagnosis is not the obvious one and there could be multiple contributors to the pathogenesis. Establishing diagnosis is important for counseling patient on disease prognosis and to guide treatment.